A COMBINATION OF CHEEK FLAP, CARTILAGE INSERTION, AND FAT TRANSFER ON POST-TRAUMA LOWER EYELID ECTROPION RECONSTRUCTION - Elfiah, Ulfa; Aprinova, Dicky Primadika (Jurnal Rekonstruksi dan Estetik, 2024)
Highlights: This study introduces an innovative approach for post-traumatic ectropion reconstruction in children by combining Mustarde rotational cheek flap, cartilage insertion, and fat transfer. This method effectively addresses the challenges of cicatricial ectropion caused by injuries or burns, leading to improved, durable, and cost-effective outcomes in restoring eyelid function and volume. Abstract: Introduction:Ectropion correction surgery is a procedure designed to restore the anterior lamella to its anatomical position. This study aims to propose a combination of cheek flap and fat transfer as a method for post-traumatic ectropion reconstruction surgery. Case Illustration:A 10-year-old girl presented with ectropion caused by scar formation and volume loss in the infraorbital region following a traumatic incident seven years prior. The procedures performed in this case included a Mustarde rotational cheek flap to reconstruct the scar tissue in the infraorbital region that led to the ectropion, pure ear cartilage insertion to repair the damaged tarsal plate or tarsus, and fat transfer to address the volume loss in the infraorbital area. The donor fat was harvested from the inguinal region Discussion: The rationale for using the Mustarde rotational cheek flap, cartilage insertion, and fat transfer was based on the wide donor area, particularly in cases where the vertical dimension exceeds the horizontal dimension. This approach is believed to yield better outcomes compared to other methods, such as skin grafts. In this case, fat transfer was employed to restore the volume lost beneath the scar tissue following trauma. This combination technique is thought to be more durable and to provide superior results compared to alternative methods, while also being economically advantageous. Conclusion: The combination of the Mustarde rotational cheek flap, cartilage insertion, and fat transfer is believed to improve the outcomes of the reconstruction procedure following scar tissue release and correction of volume loss beneath the scar.